Enzymes of the SUMO Modification Pathway Localize to Filaments of the Nuclear Pore Complex - Zhang, Hong (American Society for Microbiology, 2002)
SUMOs are small ubiquitin-related polypeptides that are reversibly conjugated to many nuclear proteins. Although the number of identified substrates has grown rapidly, relatively little is still understood about when, where, and why most proteins are modified by SUMO. Here, we demonstrate that enzymes involved in the SUMO modification and demodification of proteins are components of the nuclear pore complex (NPC). We show that SENP2, a SUMO protease that is able to demodify both SUMO-1 and SUMO-2 or SUMO-3 protein conjugates, localizes to the nucleoplasmic face of the NPC. The unique amino-terminal domain of SENP2 interacts with the FG repeat domain of Nup153, indicating that SENP2 associates with the nucleoplasmic basket of the NPC. We also investigated the localization of the SUMO conjugating enzyme, Ubc9. Using immunogold labeling of isolated nuclear envelopes, we found that Ubc9 localizes to both the cytoplasmic and the nucleoplasmic filaments of the NPC. In vitro binding studies revealed that Ubc9 and SUMO-1-modified RanGAP1 bind synergistically to form a trimeric complex with a component of the cytoplasmic filaments of the NPC, Nup358. Our results indicate that both SUMO modification and demodification of proteins may occur at the NPC and suggest a connection between the SUMO modification pathway and nucleocytoplasmic transport.